Clinical relevance of expanded quantitative urine culture in health and disease - Deen, Nadia S.; Ahmed, Akash; Tasnim, Nazifa Tabassum; Khan, Nabila (Frontiers in Cellular and Infection Microbiology, 2023)
1. "Expanded quantitative urine culture (EQUC)" is an enhanced culture protocol for the detection of viable microbes in urine specimens. Using a large volume of urine and different sets of cultural conditions, EQUC is able to uncover a wide range of bacteria and fungi (yeasts) that were otherwise undetected by the standard urinary culture. In addition to common urinary pathogens, EQUC has been shown to detect emerging and new pathogens, and commensal microbiota. Although the usefulness of EQUC protocol in clinical set up has not yet been fully established, recent studies have demonstrated that EQUC can provide valuable information regarding symptom resolution, treatment responses and diagnosis of major urinary disorders including urinary tract infections, urinary incontinence and other lower urinary tract symptoms. EQUC may also help in evaluating the utility of beneficial microbiota as biotherapeutics. This narrative minireview describes the current research findings regarding the clinical utility of EQUC in characterizing the role of urinary microbiome and uropathogens in health and disease. The literature which are written in English, available on "PubMed" and contain any of the terms-"expanded quantitative urine culture", "enhanced quantitative urine culture" and "EQUC" in the abstracts were used as the source articles to prepare this minireview.